Em busca dos rastros perdidos da memória ancestral: um estudo de Um defeito de cor, de Ana Maria Gonçalves - Zilá Bernd (Estudos de Literatura Brasileira Contemporânea)
The article provides a theoretical reflection upon the concept of traces, evoking the main authors who have defined it, such as P. Ricoeur, C. Ginzburg, J.-M. Gagnebin, E. Glissant and S. J. Pesavento, among others, and introducing termi- nological variants such as vestiges, ruins, residues, marks etc. We consider the importance of this concept in order to rethink the memory work in contemporary literary texts, especially in Ana Maria Gonçalves' novel Um defeito de cor (Record, 2010), which is an outstanding example of the recovery of African-Brazilian col- lective memory from traces.